Does Industrial Agglomeration Mitigate Fossil CO2 Emissions？An Empirical Study with Spatial Panel Regression Model. (October 2018) - Zhang, Lijun; Rong, Peijun; Qin, Yaochen; Ji, Yongyue
Abstract: This paper investigates the factors influencing industrial carbon emissions. The primary aim is to find a solution to mitigate CO2 emissions from fossil combustion with rapid economic development and urbanization in coal principally consumed areas. The paper analyzes the effects of 7 factors on industrial carbon emissions and intensity in 18 cities in Henan Province from 2005 to 2015. The factors including energy structure, the index of industrial agglomeration, proportion of state-owned enterprises, proportion of collective enterprises, degree of industrialization, urbanization, foreign investment. The study establishes six panel models to analyze the influencing mechanism before and after the implementation policy on industrial clusters and carbon reduction. The results show that the carbon locking of energy structure has a path dependence. The increase of industrial agglomeration has a huge capacity of space spillover, which has broken the high carbon lock of coal to some extent. The degree of enterprise concentration to mitigate industrial carbon emissions needs to be improved. The inhibitory effect of foreign investment on carbon emissions has begun to highlight, but it has a certain policy directivity. Urbanization and industrialization have a phased impact on industrial carbon emission and emission intensity. The spatial interaction between industrial carbon emissions and its influencing factors provide new solutions to reduce carbon emissions.